Efek modal kerja terhadap profitabilitas perusahaan rokok yang tercatat di LQ 45 - Sunardi Sunardi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
This research aims to determine the effect of working capital turnover, cash turnover, accounts receivable turnover, and inventory turnover on ROA in Cigarette Companies Listed at LQ 45 for the 2011-2020 period. This research is quantitative research that originates from the company's financial statements recorded on the company's official website for the period 2011-2020. The analysis technique used is Multiple Regression using IBM SPSS Statistics 25. The results of this study indicate that working capital turnover, cash turnover, receivable turnover, and inventory turnover affect ROA simultaneously. While partially cash turnover and inventory turnover significantly affect ROA